Punching shear strength of slab-column connections in flat plate system - Than, Than Wai (2008)
Nowadays the flat plate floor system, which is directly supported on the top of columns without drop panels and column capitals, becomes more popular and is used in apartment buildings, car park buildings and office buildings because of the benefits achieved by using this floor system. However, the disadvantage of this system is the vulnerability of the punching shear failure around the region of column. This failure can occur when the strength around the region of column is not enough to resist the stress concentrated in that region. The high stresses can concentrate around the slab-column connections due to shear force, unbalanced moment, and combination of shear and unbalanced moment. Some of the sources of these forces are the very high gravity forces, unsymmetrical layout of structure, wind and earthquake loading. When the slabs have openings near the column, uneven shear stresses that cause the punching shear failure can exist in the vicinity of column.